2020
DOI: 10.3390/jcm9041111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sacubitril/Valsartan on Device Detected Arrhythmias and Electrical Parameters among Dilated Cardiomyopathy Patients with Reduced Ejection Fraction and Implantable Cardioverter Defibrillator

Abstract: Sacubitril/valsartan therapy reduces sudden cardiac death (SCD) among patients with reduced ejection fraction (HFrEF) when compared to guidelines recommended doses of enalapril, however the mechanism is still not clear. There are few, contrasting results about the effect of sacubitril/valsartan on arrhythmias in the clinical context of dilated cardiomyopathy (DCM) and there are no clinical data about its effect on measured implantable cardioverter defibrillator (ICD) electrical parameters, such as atrial/ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…This incidence was similar between the two sexes and comparable with the incidence reported in the PIONEER-HF trial (8). Finally, we could not ascertain accurately the incidence of worsening renal function since there were only three studies which reported this endpoint in 661 patients (9,(13)(14).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This incidence was similar between the two sexes and comparable with the incidence reported in the PIONEER-HF trial (8). Finally, we could not ascertain accurately the incidence of worsening renal function since there were only three studies which reported this endpoint in 661 patients (9,(13)(14).…”
Section: Discussionsupporting
confidence: 72%
“…The markedly reduced incidence of hyperkalemia in our meta-analysis of observational studies compared to the RCTs (2% versus 12%) (3,5), may reflect less frequent serum potassium monitoring outside the RCT context. The low incidence of clinically significant hyperkalemia in the observational studies was reassuring considering the appropriate use of concomitant mineralo-corticosteroid antagonists, with rates as high as 93% in one cohort (13).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…63,64,85 and maximize the ability to improve outcome as well as quality of life 86 and ICD electrical atrial parameters. 87 • The process of reduction of left ventricular volumes, with reversal of left ventricular geometry alterations and with improvement of systolic function occurring in HF after neuro-hormonal blockade (the so-called 'left ventricular reverse remodelling') is a key factor for outcome improvement, also in terms of prevention of SCD 88,89 and is more pronounced with ARNI as compared with ACE inhibitors, thus supporting the rationale for instituting sacubitril/valsartan in all the patients who can be eligible for ARNI treatment. 90 • CRT is a very effective non-pharmacological treatment in appropriately selected patients, 91,92 and structural left ventricular reverse remodelling is a key factor in determining the clinical and outcome benefits at long term.…”
Section: Sacubitril/valsartan: Impact On Cardiovascular Mortality and On Sudden Cardiac Deathmentioning
confidence: 99%
“…The incidence of sudden cardiac death, ventricular arrhythmias and appropriate implantable cardioverter defibrillator (ICD) therapy was lower in HFrEF patients with sacubitril/valsartan compared to RAAS blockers [41][42][43][44]. In agreement, a 12-month "realworld" observational study of 167 patients with dilated cardiomyopathy due to ischemic and non-ischemic origins documented a markedly diminished incidence of ICD-detected atrial and ventricular arrhythmias following sacubitril/valsartan, together with a reduction in appropriate ICD shocks [45]. This was accompanied by a significant increase of LVEF and reduction of other echocardiographic parameters (e.g., LV end-systolic and -diastolic volumes, left-and right-atrial volume index, E/A ratio and systemic pulmonary arterial pressure) following sacubitril/valsartan [45], suggesting that antiarrhythmic effects may partly reflect an ARNI-induced reverse cardiac remodeling.…”
Section: The Effects Of Arni On Ventricular Arrhythmiasmentioning
confidence: 87%